1980
DOI: 10.1038/bjc.1980.339
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gangliosides in human leucocytes

Abstract: Summary.-Lipids extracted from leucocyte pellets with chloroform-methanol were applied to a DEAE-Sephadex column and the gangliosides were eluted with 02M sodium acetate in methanol. The eluate was desalted by Sephadex G-50 column chromatography. The purified ganglioside was spotted on the high-performance thin-layer plate. The plate was developed and sprayed with resorcinol reagents and heated.Seventeen bands of gangliosides were demonstrated in normal human leucocytes. The composition of these gangliosides w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
(9 reference statements)
2
5
0
Order By: Relevance
“…The finding that GM3 is the predominant ganglioside of normal human lymphocytes is in agreement with the results of Tsuboyama et al (1980( ), Macher et al (1981, and Westrick er a!. (1983), who were the first to use purified MN cell preparations for their analyses.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding that GM3 is the predominant ganglioside of normal human lymphocytes is in agreement with the results of Tsuboyama et al (1980( ), Macher et al (1981, and Westrick er a!. (1983), who were the first to use purified MN cell preparations for their analyses.…”
Section: Discussionsupporting
confidence: 91%
“…Hildebrand et al (1972) found only one ganglioside, GM3, in all of the 6 CLL samples studied. With the newly developed high-performance thin-layer chromatography, 4 gangliosides, GM3, GM2, GM1 and an unidentified compound with a lower TLC mobility than GMI (54.9%, 16.2%, 20.5% and 8.4%, respectively) were demonstrated in one case of CLL (Tsuboyama et al, 1980). Another one-case study (Goff ef al., 1983) found 2 major (GM3 and GD3) and 3 minor, unidentified gangliosides of higher polarity.…”
Section: Discussionmentioning
confidence: 94%
“…The initial BKV infection of a child likely occurs in the tonsils, where GD1b and GT1b have both been observed (48). BKV infection then progresses to peripheral blood mononuclear cells, from which these two gangliosides have also been extracted (50). Finally, BKV remains subclinical for the lifetime of the host in the kidney, where it has been shown that GD1b and GT1b are present in both cortical tubular and medullary tissue (28).…”
Section: Discussionmentioning
confidence: 99%
“…These sialogangliosides have been found as receptors on the surface of mononuclear cells (27) and also on cortical tubular and medullary tissue (28) and have been implicated in erythrocyte hemaglutination seen as a result of BKV infection. This activity is sensitive to neuraminidase treatment, which removes the terminal sialic acid of many gangliosides and glycoproteins (29).…”
Section: Discussionmentioning
confidence: 99%